Systematized review study on biochemical biomarkers of overtraining - Carneiro, Tulio Oliveira; Orso, Robson Silva Araujo; Gargioni, Ligia Fogolin; Crisóstomo, Isabella Galvão; Miguel, Natanne Dias Meira; Júnior, Augusto Carlos Zaccarone; Almeida, Danilo de Lima; Ravagnani, Priscilla A. L.; Sakamoto, Sabrina Ramires; Duarte, Ana Claudia Garcia de Oliveira; Fabrizzi, Fernando (Seven Editora, 2023)
In sports, the demand for victory increasingly places the professional athlete face to face with the incessant search for both physical, tactical, and strategic performance, since these factors are fundamental to obtaining a victory. However, overtraining can lead to disorders that are harmful to the athlete’s health. Objective: systematized review on biochemical biomarkers of overtraining. The PRISMA Checklist was used for development and the PICO strategy for data extraction. Inclusion criteria were articles with primary data published in the last 10 years, in Portuguese, English and Spanish that were directly related to the central objective of the study. Results: After using all the inclusion and exclusion criteria, 11 articles were chosen for the development of the article, which was directly related to the theme of the study. In these articles, four major classes of molecules with potential biomarkers of overtraining were obtained: -related to intermediary metabolism; - related to the organism’s redox profile; -with hormonal function, and; -with immune function. DOI:https://doi.org/10.56238/alookdevelopv1-018